Evaluating the effectiveness of Parent Empowerment (COPE) program on participation of mothers of preterm infants hospitalized in NICUs of hospitals affiliated to Isfahan University of Medical Sciences and Health Services, 2009-2010 - Alaee Karhrouy, fatemeh; Jafari Mianaie, soheila; Rassouli, maryam; Zayeri, farid (Advances in Nursing & Midwifery, 2014)
Abstract Background and aim: The birth of a preterm infant is a stressful event for parents. Because of special nature of the Neonatal Intensive Care Unit (NICU) environment, parents of infants admitted to a neonatal intensive care unit experience higher levels of tension, compared with parents of healthy infants the mother’s physical and psychological condition may negatively influence early and suitable mother–infant relationship, the mother’s participation in her infant care and the infant’s long-term developmental outcome. The purpose of this study was to evaluate the effectiveness of Creating Opportunities for Parent Empowerment (COPE) program on participation of mothers of preterm infants hospitalized in NICUs of hospitals affiliated to Isfahan University of Medical Sciences and Health Services. Method and material: A randomized clinical trial was conducted with 90 mothers of premature infants hospitalized in the neonatal intensive care units. COPE mothers received 2 intervention sessions of audiotaped and printed materials with workbook. This program consisted of information and behavioral activities about the appearance and behavioral characteristics of preterm infants and how best to parent them. Duration between sessions was 2 to 4 days. Data were collected by a questionnaire.The participation was evaluated just 2 to 4 days after second phase. Results: The mea score of mothers’ participation in experiment group was 9.14±0.84 and 9.43±1.06 for the first and second phase of post -test.Mothers in the Creating Opportunities for Parent Empowerment program reported significantly more participation in their infants care (p<0.001). Discussion and Conclusion: Creating Opportunities for Parent Empowerment program diminished mothers enhance the amount of mother’s participation. This study showed that early interventions during neonatal hospitalization and educational behavioral information in written form may have positive effect on maternal psychological condition and participation. Key words: nurse, parents’ empowerment , participation, preterm infant, randomized clinical trial